PENGARUH INVENTORY TURNOVER (ITO) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PT GAJAH TUNGGAL Tbk PERIODE 2013-2023 - Ika Wahyu Dwi Velinia; Lina Nofiana (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of Inventory Turnover and Total Asset Turnover on Return On Assets at PT Gajah Tunggal Tbk for the 2013-2023 period. The research method uses descriptive quantitative methods. Research results: Inventory Turnover has no significant effect on Return On Assets. The correlation coefficient value is 0.041. The coefficient of determination value is 0.2%. The t value is 0.239 < ttable 1.860 with a significance value of 0.817> 0.050. Total Asset Turnover does not have a significant effect on Return On Assets. The correlation coefficient value is 0.225. The coefficient of determination value is 5%. The t value is 0.686< t table 1.860 with a significance value of 0.512> 0.050. Simultaneously, Inventory Turnover and Total Asset Turnover do not have a significant effect on Return On Assets at PT Gajah Tunggal Tbk for the 2013-2023 period. The correlation coefficient value is 0.239. The coefficient of determination value is 5.7%. The t value is 0.243 < t table 4.459 and the significance value is 0.790 > 0.050.